Brain development using a multicomponent intravenous lipid emulsion in preterm infants - Katherine M. Ottolini; Julius Ngwa; Sudeepta K. Basu; Kushal Kapse; Melissa Liggett; Jonathan Murnick; Catherine Limperopoulos; Nickie Andescavage (BMC Pediatrics)
Abstract Background Intravenous lipid emulsions are an essential component of nutritional support for very preterm infants. Many neonatal intensive care units have transitioned from traditional soybean oil-only to fish oil-containing multicomponent lipid emulsions, but the neurodevelopmental implications have not been well-explored. The primary aim of this study was to assess extrauterine third trimester brain growth in very preterm infants supported with soybean oil-only compared to fish-oil containing multicomponent lipid emulsions; white matter development and neurobehavioral regulation at term were also investigated. Methods Human milk-fed very preterm infants (born less than or equal to 32 weeks’ gestation) receiving either soybean oil-only (before 2019) or multicomponent (after 2019) lipid emulsions underwent quantitative brain MRI (volumetric growth and white matter development) and neurodevelopmental assessment (Neonatal Intensive Care Unit Network Neurobehavioral Scale) at term-equivalent age. Analyses were adjusted for age at birth and term assessments, as well as clinically significant covariates. Results 92 infants (61 soybean, 31 multicomponent) were included (mean [SD] birth gestational age: 27.3 [2.3] weeks). Soybean oil-only infants demonstrated smaller brainstem volumes (β [95% CI] = -0.5 [-0.8,-0.1], p = .007); additionally less mature white matter development (mean diffusivity [MD, mm2/second x10− 3] and fractional anisotropy [FA]) in the corpus callosum (MD genu: β = 0.10 [0.01, 0.20], p = .04; splenium: β = 0.14 [0.04, 0.24], p = .006), posterior limbs of internal capsule (MD right (R): β = 0.05 [0.02, 0.08], p = .004, left (L): β = 0.04 [0.01, 0.08], p = .01; FA R: β = -0.03 [-0.06, -0.00], p = .03), and brainstem (FA R: β = 0.07 [0.04, 0.10], p < .001, L: β = 0.05 [0.02, 0.09], p = .002); and lower quality of movement (β = -0.54 [-0.97, -0.11], p = .02) and higher state-related stress (β = 1.41 [0.14, 2.83], p = .04). Conclusions Very preterm infants supported with a fish-oil containing multicomponent compared to soybean oil-only lipid emulsion demonstrated improved regional brain growth, as well as evidence of enhanced white matter microstructural organization and neurobehavioral regulation, at term corrected age. Trial registration Clinical trial number: Not applicable.